1978
DOI: 10.1111/j.1365-2141.1978.tb07110.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Antibodies in Chronic Lymphatic Leukaemia

Abstract: In chronic lymphocytic leukaemia a factor in patients' serum enhances the in vitro viability of the abnormal cells and this has been identified as an antibody. The activity of this factor can be removed by interaction with anti-immunoglobulin and by ammonium sulphate precipitation with a degree of saturation in excess of 46%. Cohn fractionation and chromatography with A-50 Sephadex show that the factor is not a complex but an immunoglobulin. No activity is removed after reaction of sera with 2-mercapto-ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, CIC in an individual may arise from sources other than tumor activity. Antibody [19], antiidiotype [5,15,23] and other altered self components [2,6,18] have been detected in CIC of cancer patients. Since most CIC detection assays are antigen nonspecific, it is not surprising that the clinical utility of CIC analysis in human cancer has been controversial and limited [6,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, CIC in an individual may arise from sources other than tumor activity. Antibody [19], antiidiotype [5,15,23] and other altered self components [2,6,18] have been detected in CIC of cancer patients. Since most CIC detection assays are antigen nonspecific, it is not surprising that the clinical utility of CIC analysis in human cancer has been controversial and limited [6,28].…”
Section: Introductionmentioning
confidence: 99%
“…We have found that antilymphocyte antibodies present in sera from these patients affect the behaviour of the CLL cells and that these antibodies cross-react extensively from patient to patient [9]. Their biological activ ity can be demonstrated in vitro through the enhancement of leukaemic cell viability and this suggested that lymphocyte anti bodies may be responsible for longevity of CLL cells in vivo.…”
Section: Introductionmentioning
confidence: 79%
“…This finding does not necessarily rule out an en hancing function for the antibody and it may suggest that antibody is being taken up from the serum by the lymphocytes, most prob ably by the M cells. Evidence from 'washing experiments' shows that antibody can be removed from CLL cells and this both re duces their viability and the 'M'-rosetting capacity [9].…”
Section: Discussionmentioning
confidence: 99%